Joint estimation of the natural rate of interest, the natural rate of unemployment, expected inflation, and potential output - Luca Benati; Giovanni Vitale (European Central Bank (ECB), 2007)
We jointly estimate the natural rate of interest, the natural rate of unemployment, expected inflation, and potential output for the Euro area, the United States, Sweden, Australia, and the United Kingdom. Particular attention is paid to time-variation in (i) the data-generation process for inflation, which we capture via a time-varying parameters specification for the Phillips curve portion of the model; and (ii) the volatilities of disturbances to inflation and cyclical (log) output, which we capture via break tests. Time-variation in the natural rate of interest is estimated to have been comparatively large for the United States, and especially for the Euro area, and smaller for Australia and the United Kingdom. Overall, natural rate estimates are characterised by a significant extent of uncertainty.
Keywords: E31; E32; E52; 330; monetary policy; Natural rate of interest; time-varying parameters; Zins; Zinstheorie; Natürliche Arbeitslosenquote; Inflationserwartung; Produktionspotenzial; Schätzung; Eurozone; EU-Staaten; Australien; Großbritannien; Schweden; USA